Occurrence of dry and wet weeks over Maharashtra - GORE, P. G.; THAPLIYAL, V. (MAUSAM, 2000)
Based on the daily rainfall data of the past 90 years (1901-90), the initial and conditional probabilities of a wet week and the probabilities of 2 and 3 consecutive wet weeks have been computed for all the districts of Maharashtra during the southwest monsoon season by using Markov Chain model. A temporal and spatial distribution of probabilities of wet weeks have been studied in detail. Most of the districts show the highest probability of wet weeks during July. A few number of the districts show the second highest probability during August. The western and northeastern parts of the state show 10-16 wet weeks with high probability. The high rainfall districts along the west coast show high wet week probabilities during most of the period of the season. A few number of the districts from moderate rainfall zone, show high probability of a wet week during, July and August. A persistency in rainfall is noticed in only extreme western parts of the state. The east-west variation along 19° N shows 'L' shaped pattern for the high probability wet weeks. While, the north -south variation of the wet weeks with high probability shows a sinusoidal curve from north to south.